IMMEDIATE EFFECT OF SMARTPHONE USE ON BALANCE AND MUSCLES ACTIVITY OF ABDOMINAL AND LUMBAR - Hwang, Hyun-Chul; Kim, So-Hee; Kim, Tae-Ho (International Journal of Psychosocial Rehabilitation, 2020)
It was reported that maintaining a slouched posture continuously for extended periods not only causes pain in the lumbar and neck but also may negatively affect proprioception.This study was aimed to compare the immediate effects of balance and muscle activity of abdominal lumbar muscle activity according to the posture of using the smartphone. The healthy fifteen subjectswere asked to play the game for 3 minutes. They played the game first with the posture of raising the smartphone to the height of the collarbone while straightening the back consciously and then with the natural posture without straightening the back consciously.When straightening the back consciously, the activity of the abdominal muscle and the erector spinae was high, and the moving range of the stability limit was also high. When not consciously straightening the back, the activity of the abdominal muscle and the erector spinae was low, as was the moving range of the stability limitTherefore, to prevent the neck from bending forward and the body from slouching, consciously straightening the back is deemed the correct posture.